2011
DOI: 10.1038/eye.2010.192
|View full text |Cite
|
Sign up to set email alerts
|

Ocular loiasis in London 2008–2009: a case series

Abstract: Although ocular loiasis is endemic in West Africa, European ophthalmologists in areas of diverse ethnicity should be aware that it is presenting increasingly frequently, that there is often no history of recent travel abroad, and that loiasis is a differential diagnosis for any 'at-risk' patient with an unexplained foreign body sensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…L. loa infestation presenting as the "African eye worm" has been well reported as a trans-border disease imported from endemic regions of the world to other non endemic countries. This is seen in several case reports from Europe, Latin America, Asia and the United States of individuals who have imported the parasite by travelling to or living in endemic regions in Central and West Africa [11,12,13,14]. A review of over a hundred infected individuals identified the patients to have made contact with three countries namely Cameroon, Nigeria and Gabon [15].…”
Section: Resultsmentioning
confidence: 99%
“…L. loa infestation presenting as the "African eye worm" has been well reported as a trans-border disease imported from endemic regions of the world to other non endemic countries. This is seen in several case reports from Europe, Latin America, Asia and the United States of individuals who have imported the parasite by travelling to or living in endemic regions in Central and West Africa [11,12,13,14]. A review of over a hundred infected individuals identified the patients to have made contact with three countries namely Cameroon, Nigeria and Gabon [15].…”
Section: Resultsmentioning
confidence: 99%
“…It is endemic in West and Central Africa where prevalence in some areas is as high as 50 % [ 1 , 2 ] and constitutes one of the main reasons for locals to seek medical advice. Two cases of ocular loiasis have been reported so far in Spain [ 3 , 4 ], three in the USA [ 5 - 7 ] and other isolated cases in Brazil [ 8 ], Italy, Norway, Australia, South Korea and the United Kingdom [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Until recently, it was limited to residents of these countries, but increased tourism and emigration have extended its impact in Europe. An estimated 30% of long-term visitors are infected by this parasite.…”
mentioning
confidence: 99%
“…2,3 A 68-year-old woman with 20/20 vision presented complaining of floaters and a "snake-like" shadow moving in her left eye. Examination revealed a mobile worm in the vitreous cavity without signs of ocular inflammation (Figures 1-3).…”
mentioning
confidence: 99%